Peranan Belanja Pendidikan, Kesehatan dan Jumlah Penduduk Miskin terhadap IPM di Kabupaten Tanah Laut - Sopiah, Siti; Siregar, Syahrituah (PPJP ULM, 2023)
This research determines Education Expenditure, Health, and Total Poverty Population on HDI in Tanah Laut Regency 2009-2018. This research was conducted in Tanah Laut Regency by taking secondary data and then tested by taking a regression analysis model and knowing it consists of a partial test (t test) and simultaneous test (F test). The results of this study indicate that simultaneously Education Expenditure, Health Expenditure, and Total Poverty have a significant effect on the HDI.